Tinjauan Yuridis Pertanggungjawaban Pidana Pelaku Pencurian dengan Pemberatan (Studi Putusan No. 702/Pid.B/2025/PN Tjk) - Limantara, Benny Karya; Putra, Dharma Laury (CV. Rayyan Dwi Bharata, 2026)
This study aims to analyze the criminal liability of perpetrators of aggravated theft and the judicial considerations applied in Decision of the Tanjungkarang District Court Number 702/Pid.B/2025/PN Tjk. The research focuses on the application of Article 363 of the Indonesian Criminal Code, the form of criminal responsibility imposed on the offender, and its conformity with the principles of justice and proportionality. This research employs a normative juridical method using statutory and case approaches, supported by library research. The findings indicate that the defendant’s conduct fulfills the elements of actus reus and mens rea, thereby justifying criminal liability. However, the sentence imposed is relatively lenient compared to the maximum penalty prescribed under Article 363 of the Criminal Code, raising concerns regarding the consistent application of the principle of proportionality. This study is expected to contribute to the development of criminal law, particularly in strengthening judicial consistency in adjudicating cases of aggravated theft.